Study on livelihood sustainability and rural revitalisation policy effects of poverty-eradicating households based on DID model analysis - Zhang, Jiamei; Lei, Weijie; Yu, Jia; Li, Le (Transactions on Economics, Business and Management Research, 2024)
China has achieved a comprehensive victory in the battle against poverty. At present, China is accelerating the effective connection between consolidating the results of poverty eradication and rural revitalisation. Based on the SLA framework, this paper constructs a livelihood sustainability indicator system and evaluates it through the entropy weight method, takes Gannan Soviet District as the study area, and based on the two-period DID model, empirically examines the impact of the policy of consolidating and expanding the results of poverty alleviation and rural revitalisation on the sustainability of the livelihoods of the households that have been lifted out of poverty, using the two-period panel data in 2020 and 2022 of the 243 farming households. The findings show that the policy of consolidating and expanding the effective linkage between poverty eradication and rural revitalisation has a significant driving effect on the livelihood sustainability of farm households, increasing the level of livelihood sustainability of farm households by 11.3%, and the conclusion remains reliable after the robustness test. Heterogeneity analyses found that the policy contributed more to the livelihood sustainability level of poverty-eradicating households whose head had a high level of education. The policy has a more significant positive effect on the livelihood sustainability of labour-led and agriculture-led households out of poverty than part-time employment